A Framework of Eco-innovation Strategies and Competitive Advantages in Contractor Firms - Siti Sarah Mat Isa; Nazirah Zainul Abidin; Izyan Yahaya (International Journal of Supply Chain Management, 2019)
Eco-innovation (EI) is vital for the contractor firm in order to reduce all the negative impacts of construction activities on the environment and reach governments’ green requirement. EI strategies refer to the capabilities of a firm to build an environment that supports innovation and green practices. The contribution of the construction industry towards environmental degradation due to rapid development in the urban area and unsustainable way of past construction had increase awareness toward EI. However, the study on EI in the construction industry has received much less attention even though EI capable to improve contractor firm’s competitiveness and sustaining business endeavour. Thus, this paper aims to identify appropriate strategies which drive and enhance implementation of EI in the contractor firms. The dynamic capabilities theory is adopted as the premise to examine a firm’s ability to sense, seize and reconfigure its capabilities to accomplish the environmental goal in its business strategy. A literature review is carried out to determine the EI strategies that crucial to improve the conservative construction practices toward green. Content analysis is adopted through interpretation and text data coding. The study unveils five EI strategies which are human resources development, technology advancement, collaboration and networking, knowledge empowerment and management proactiveness strategy. A framework representing the EI strategies that beneficial to contractor firms to become eco-innovative and competitive is presented. This framework will be a guide to contractor firm to enhance firm competitive advantages and drive environmental sustainability simultaneously.